Exploration Capabilities, Digital Competence, Innovation, and Sustainable Competitive Advantage: Does Entrepreneurial Agility Matter? - Arwani, Mokhamad; Maskudi; Darmanto, Susetyo; Ariyanto, Didik (Jurnal Aplikasi Manajemen, 2025)
Entrepreneurial agility is a crucial factor in Indonesia's online business. The sector is important in achieving the 2030 Sustainable Development Goals (SDGs), and supports the digital economy focus in RIRN 2017-2045. However, competition among online businesses is very tight. The purpose of this study was to examine the sustainable competitive advantage of online businesses based on explorative capabilities, digital competency, and innovative behavior. Furthermore, the study aimed to analyze the mediating role of entrepreneurial agility. The design was a quantitative type with data collection using questionnaires. The sample consisted of 153 MSMEs operating online businesses in Semarang City and its surrounding areas. Data collected with purposive sampling. The data was processed using partial least squares structural equation modeling (SEM-PLS) through SmartPLS 4. The results showed that explorative capabilities, digital entrepreneurial competency, and innovative behavior have a positive effect on entrepreneurial agility. Further findings demonstrated that digital entrepreneurial agility has a positive impact on achieving sustainable competitive advantage. The study had theoretical implications for highlighting the importance of digital entrepreneurial agility in improving MSMEs' sustainable competitive advantage. The novelty study enriched the dynamic capability theory by offering digital competency as a key to sustainable business. Managerial implications emphasized the need for digital business managers to prioritize innovative behavior in response to market competition.